Synthesis, physical-chemical and biological properties of 1.8-disubstituted of theobromine. V. 8-Benzylidenhydrazino-1-p-methylbenzyltheobromines - Ivanchenko, D. G.; Іванченко, Дмитро Григорович; Иванченко, Д. Г. (Запорізький державний медичний університет, 2015)
The problem of searching biologically active compounds amidst xanthine derivatives is a crucial one and is an issue for long-term investigation. Aim. In order to find new biologically active compounds among xanthine derivatives, undescribed earlier 8-benzylidenhydrazino-1-pmethylbenzyltheobromines have been synthesized. Methods and results. Reaction of 1-p-methylbenzyl-8-bromoxanthine with the excess of hydrazine hydrate in the aqueous dioxane is implemented through formation of 8-hydrazine-1(4-methylbenzyl)theobromine. Through the interaction of 8-hydrazinetheobromine with aldehydes in aqueous propan-2-ol respective 8-benzylidenhydrazino-1-p-methylbenzyltheobromines have been obtained. Structure of synthesized compounds has been definitely proved by NMR-spectroscopy. Conclusions. Molecular and pharmacological descriptors of obtained substances have been calculated. The antioxidant activity of the obtained compounds has been explored. Priorities for further search of biologically active compounds in a range of xanthine derivatives have been set out. Проблема пошуку біологічно активних сполук серед похідних ксантину є актуальною та перспективною. З метою створення нових біологічно активних сполук похідних ксантину синтезували неописані в літературі 8-бензиліденгідразино-1-п-метилбензилтеоброміни. Реакцією 1-п-метилбензил-8-бромотеоброміну з надлишком гідразину гідрату в середовищі водного діоксану отримали 1-п-метилбензил-8-гідразинотеобромін. Взаємодія 8-гідразинотеоброміну з альдегідами в середовищі водного пропанолу-2 призвела до утворення відповідних 8-бензиліденгідразино-1-п-метилбензилтеобромінів. Структура сполук однозначно доведена методом ПМР-спектроскопії. Для синтезованих речовин розрахували молекулярні та фармакологічні дескриптори. Дані, що одержали, свідчать про доцільність наступних досліджень in vitro та in vivo. Вивчили антиоксидантну активність (in vitro). Встановили пріоритети для пошуку біологічно активних сполук в ряді похідних ксантину. Проблема поиска биологически активных соединений среди производных ксантина актуальна и перспективна. С целью создания новых биологически активных соединений производных ксантина синтезировали неописанные в литературе 8-бензилиденгидразино-1-п-метилбензилтеобромины. Реакцией 1-п-метилбензил-8-бромтеобромина с избытком гидразин гидрата в среде водного диоксана получили 1-п-метилбензил-8-гидразинотеобромин. Взаимодействие 8-гидразинотеобромина с альдегидами в среде водного пропанола-2 привело к образованию соответствующих 8-бензилиденгидразино-1-п-метилбензилтеоброминов. Структура синтезированных соединений однозначно доказана методом ПМР-спектроскопии. Рассчитаны молекулярные и фармакологические дескрипторы. Полученные данные свидетельствуют о целесообразности дальнейших исследований in vitro и in vivo. Изучена антиоксидантная активность (in vitro). Установлены приоритеты для дальнейшего поиска биологически активных соединений в ряду производных ксантина.
Синтез, фізико-хімічні та біологічні властивості 1,8-дизаміщених теоброміну. V. 8-Бензиліденгідразино-1-п-метилбензилтеоброміни
Синтез, физико-химические и биологические свойства 1,8-дизамещённых теобромина. V. 8-Бензилиденгидразино-1-п-метилбензилтеобромины
Keywords: Xanthine; Organic Synthesis; NMR-spectroscopy; Acute Toxicity; Antioxidant Effect; ксантин; органічний синтез; ПМР-спектроскопія; гостра токсичність; антиоксидантний ефект; органический синтез; ПМР-спектроскопия; острая токсичность; антиоксидантный эффект